Penyisihan Kadar Fosfat Pada Limbah Cair Laundry Menggunakan Biokoagulan Cangkang Kepiting (Brachyura) - Mashitah, Siti; Daud, Syarfi; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biocoagulant is a natural coagulant that has an active substance and has a role as cationic which is able to bind colloidal particles in water. Chitosan is a non-toxic, easy-to-degrade and polyelectrolyte biocogulant that can be found in crustacean animals especially in crabs (Brachyura). The availability of crab shell waste has a huge potential to be used as raw material for making chitosan. High concentration of detergent in water can cause water quality to decrease and environmental pollution in the form of increase of phosphate level, so that the previous processing is needed by using coagulation-flocculation method. The research process was done gradually starting from the extraction of crab shells to chitosan by deproteination process, demineralization, and deacetylation, followed by Coagulation-flocculation method. The study was conducted by varying the dose of coagulant by 150 mg / L, 200 mg / L, 250 mg / L and 300 mg / L. The effluent was then analyzed by the laboratory, for COD parameters referring to SNI 06-6989.2-2004, and phosphate refers to SNI 06-6989.31-2005. The result of the analysis was then compared with the PERMENLH / 5/2014 quality standard. Based on the laboratory results, after analyzing the concentration of the parameters tested, it showed that the maximum allowance of phosphate parameters were 81.84% respectively at 200 mg / L coagulant dose with stirring speed of 150 rpm for 2 min and 60 rpm for 15 min followed by deposition for 30 min.Keywords:Biocoagulant, chitosan, coagulation-flocculation